PENGARUH WORK LIFE BALANCE DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA LAYANAN DIMEDIASI KEPUASAN KERJA PADA PEGAWAI KANTOR PELAYANAN PAJAK PRATAMA BENGKULU DUA - Lavena, Betta (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This research The Influence of Work Life Balance and Employee Engagement on Service Performance is Mediated by Job Satisfaction in Bengkulu Dua Pratama Tax Service Office Employees either eksogen or endoogen. Based on the results of the research and discussion described above, the results can be concluded as follows: 1. Shows that there is a positive relationship between work life balance and service performance 2. There is no influence between employee engagement on service performance 3. There is not influence between work life balance on job satisfaction 4. There is an influence between employee engagement and job satisfaction  5. There is no influence between job satisfaction and service performance 6. Job satisfaction does not mediate the influence of work life balance on service performance, 7. Job satisfaction does not mediate the relationship between employee engagement and service performance, this is indicated by the T statistic value of 1.587 (<1.967) and the significance value of p 0.113 (>0.05). This value shows that H7 is rejected. Keywords: Work Life Balance, Employee Engagement, Service Performance and Job Satisfaction